Validation of the Applied Biosystems RapidFinder Shiga Toxin–Producing E. coli (STEC) Detection Workflow. (27th November 2019) - Cloke, Jonathan; Matheny, Sharon; Swimley, Michelle; Tebbs, Robert; Burrell, Angelia; Flannery, Jonathan; Bastin, Benjamin; Bird, Patrick; Benzinger, M Joseph; Crowley, Erin; Agin, James; Goins, David; et al.
Abstract: The Applied Biosystems™ RapidFinder™ STEC Detection Workflow (Thermo Fisher Scientific) is a complete protocol for the rapid qualitative detection of Escherichia coli (E. coli) O157:H7 and the "Big 6" non-O157 Shiga-like toxin-producing E. coli (STEC) serotypes (defined as serogroups: O26, O45, O103, O111, O121, and O145). The RapidFinder STEC Detection Workflow makes use of either the automated preparation of PCR-ready DNA using the Applied Biosystems PrepSEQ™ Nucleic Acid Extraction Kit in conjunction with the Applied Biosystems MagMAX™ Express 96-well magnetic particle processor or the Applied Biosystems PrepSEQ Rapid Spin kit for manual preparation of PCR-ready DNA. Two separate assays comprise the RapidFinder STEC Detection Workflow, the Applied Biosystems RapidFinder STEC Screening Assay and the Applied Biosystems RapidFinder STEC Confirmation Assay. The RapidFinder STEC Screening Assay includes primers and probes to detect the presence of stx1 (Shiga toxin 1), stx2 (Shiga toxin 2), eae (intimin), and E. coli O157 gene targets. The RapidFinder STEC Confirmation Assay includes primers and probes for the "Big 6" non-O157 STEC and E. coli O157:H7. The use of these two assays in tandem allows a user to detect accurately the presence of the "Big 6" STECs and E. coli O157:H7. The performance of the RapidFinder STEC Detection Workflow was evaluated in a method comparison study, in inclusivity and exclusivity studies, and in a robustness evaluation. The assays were compared to the U.S. Department of Agriculture (USDA), Food Safety and Inspection Service (FSIS) Microbiology Laboratory Guidebook (MLG) 5.09: Detection, Isolation and Identification of Escherichia coli O157:H7 from Meat Products and Carcass and Environmental Sponges for raw ground beef (73% lean) and USDA/FSIS-MLG 5B.05: Detection, Isolation and Identification of Escherichia coli non-O157:H7 from Meat Products and Carcass and Environmental Sponges for raw beef trim. No statistically significant differences were observed between the reference method and the individual or combined kits forming the candidate assay using either of the DNA preparation kits (manual or automated extraction). For the inclusivity and exclusivity evaluation, the RapidFinder STEC Detection Workflow, comprising both RapidFinder STEC screening and confirmation kits, correctly identified all 50 target organism isolates and correctly excluded all 30 nontarget strains for both of the assays evaluated. The results of these studies demonstrate the sensitivity and selectivity of the RapidFinder STEC Detection Workflow for the detection of E. coli O157:H7 and the "Big 6" STEC serotypes in both raw ground beef and beef trim. The robustness testing demonstrated that minor variations in the method parameters did not impact the accuracy of the assay and highlighted the importance of following the correct incubation temperatures